Application of functional metagenomics for isolation and screening of antimicrobial activity of antarctic soil microorganisms - Rangasamy, Premmala (2016)
Thousands of secondary metabolites have been identified from the culture of Gram positive, Gram negative and filamentous fungi that have been isolated from the Antarctic environment and since the year 2002. About 130 to 140 of these natural products have been used in human medicine, veterinary medicine and agriculture as pesticides. Bacteriocin production is also known as common ability among soil bacteria to outcompete competitor for resources including nutrient and water. Such ability is expected to be essential to the survival in the harsh environmental condition in Antarctica. In order to understand if Antarctic soils harbour novel bacteriocins with potential medical application, a functional metagenomic screening need to be conducted using the environmental DNA of the soil. Soil DNA extraction were done by using the Epicenter Meta-g-nome DNA extraction kit and the construction of metagenomic library were done by using the CopyControl Fosmid Library Construction kit from Epicenter. Two libraries were constructed and screened with different types of pathogens using the double agar layer method and incubated overnight at 37°C. Inhibition around the clones were observed the next day. Positive clones were picked for further screening. Positive clones were sent for Illumina next generation sequencing (NGS). The responsible gene that were identified is further cloned into an expression vector to confirm the production of antibiotic activity. Further screening were done by purifying the selected clone with C18 cartridge using the solid phase extraction method (SPE) with different percentage of solvent fractions. SPE products were evaporated using the microcentrifuge vapour evaporator at 30°C and were tested on the bacteria using the well diffusion method at the concentration of 350mg/ml. Inhibition zone were observed. By constructing two separate fosmid libraries which in total encompassed >15, 000 clones, 4 fosmid clones showing positive inhibition against Klebsiella pneumoniea were detected. BLAST results based on the DNA contigs generated using illumina NGS revealed that the clones carried periplasmic thiol-disulfide interchange protein DsbA gene and pathways related to isoprenoids for quinones and tyrosine, and phenylalaline branches from chorismate. Virtual screening using Antibiotics and Secondary Metabolites Shell (Antismash) server corroborated our observation that the selected clones harboured bacteriocin production gene. We have attempted to purify the bacterial product using C-18 solid phase extraction and had obtained fraction (80% water, 20% methanol) which conserved the antibacterial effect against Klebsiella pneumoniea. The fraction was sent for a liquid chromatography – mass spectrometry (LCMS) analysis and it showed Nalidixic acid which could be the responsible metabolite. Further screening need to be done.